Gauging the impact of the strength of patent systems on renewable energy consumption - Alexiou, Constantinos (Elsevier, 2023)
In recent years, renewable energy consumption has been at the centre stage of academic debate. Little is however known about the potential impact of the strength of patent systems (IPRs) and renewable consumption. This study addresses this issue using a GMM methodological framework for a panel of 47 developed and developing economies over the period 1998–2017. To the best of our knowledge this is the first study where two alternative indices that measure differences in strength of patent systems are employed to explore the underlying relationship whilst at the same time controlling for other potential determinants of renewable energy consumption. We find that protection of intellectual property rights across nearly all estimated models and country groups tends to have a negative impact on renewable energy consumption whilst a convex relationship is established when nonlinearities are explored. Finally, the global financial crisis is found to have a negative impact on renewable energy in both developed and developing economies. Further probing indicates that in a depressed economic environment the strength of IPRs might have a significant role to play in encouraging more renewable energy consumption.
Keywords: Renewable energy consumption; Intellectual property rights; Global financial crisis; Developed and developing economies; Generalized method of moments